ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI PROVINSI GORONTALO - Muhamad Rofi'i; Dwi Susilowati; Zainal Arifin (Jurnal Ilmu Ekonomi, 2021)
The pupose of this research of The research analyzethe effect to Gross Domestic Regional Product (GRDP), Educatioan (EDU), and Health (HLT) on poverty in the ptovince Gorontalo. In research used quantitative research with a secondary kind of data sourced from Statistical Center of Gorontalo province, the analysis use in this study is the regression of the panel data with selected Random Effect model. The research shows result of wich are as follows : 1). In variabel economic growth, education and health are partially affected negatively and significantly on the poverty level in Gorontalo province 2). In variabel economic growth, education and health simultanously have an effect on the poverty level in Gorontalo province. In this study it was concluded that the economic growth variable had a negative and significant effect on the poverty level with a probability value of 0.0008 and a coefficient of -0.760148. The education variable that uses the average length of schooling has a negative and significant effect on the poverty level with a probability value of 0.0000 and a coefficient of -2.971700. The health variable has a negative and significant effect on the poverty level with a probability value of 0.0256 and a coefficient of -0.374535.